Let $a$, $b$ and $c$ be non-negative numbers such that $ab+ac+bc\neq0$ and $a+b+c=1$.

Prove that: $$\frac{a}{\sqrt[3]{a+b}}+\frac{b}{\sqrt[3]{b+c}}+\frac{c}{\sqrt[3]{c+a}}\leq\frac{31}{27}$$

The equality occurs for $(a,b,c)=\left(\frac{19}{27},\frac{8}{27},0\right)$.

This inequality is similar to the following inequality, which was proposed by Walther Janous.

For all non-negatives $x$, $y$ and $z$ such that $xy+xz+yz\neq0$ prove that: $$\frac{x}{\sqrt{x+y}}+\frac{y}{\sqrt{y+z}}+\frac{z}{\sqrt{z+x}}\leq\frac{5}{4}\sqrt{x+y+z}$$

My proof:

By Cauchy-Schwarz $$\left(\sum_{cyc}\frac {x}{\sqrt {x+y}}\right)^2\leq\sum_{cyc}\frac{x(2x+4y+z)}{x+y}\sum_{cyc}\frac{x}{2x+4y+z}.$$ Id est, it remains to prove that $$\sum_{cyc}\frac{x(2x+4y+z)}{x+y}\sum_{cyc}\frac{x}{2x+4y+z}\leq\frac{25(x+y+z)}{16}$$ or $$\sum_{cyc}(8x^6y+72x^6z-14x^5y^2+312x^5z^2-92x^4y^3+74x^4z^3+$$ $$+122x^5yz+217x^4y^2z+143x^4z^2y+564x^3y^3z+1338x^3y^2z^2)\geq0$$ or $$\sum_{cyc}2xy(4x+y)(x-3y)^2(x+2y)^2+$$ $$+\sum_{cyc}(122x^5yz+217x^4y^2z+143x^4z^2y+564x^3y^3z+1338x^3y^2z^2)\geq0,$$ which is obvious.

If we want to use a similar way for the starting inequality, we need to use Holder, which gives very big numbers.

Maybe there is another reasoning?

Thank you!

  • $\begingroup$ Since $c=1-a-b$ how about rewriting the LHS of the inequality as a function $f(a,b)$ which defines a surface. Then find maxima of the surface. $\endgroup$ – Χpẘ Apr 9 '17 at 21:51
  • $\begingroup$ So, you have a Holder solution although the coefficients are very big? $\endgroup$ – River Li Jul 3 at 4:23
  • $\begingroup$ @River Li No, I have no solution. I can get inequality after using Holder, but I can not prove it. $\endgroup$ – Michael Rozenberg Jul 3 at 4:26

With computer, here is an ugly solution:

WLOG, assume that $c = \min(a, b, c).$ Since $x^{2/3}, x \ge 0$ is concave, we have \begin{align} \frac{b}{\sqrt[3]{b+c}} + \frac{c}{\sqrt[3]{c+a}} &= \frac{b}{b+c}(b+c)^{2/3} + \frac{c}{c+a}(c+a)^{2/3}\\ &\le \Big(\frac{b}{b+c} + \frac{c}{c+a}\Big)\left(\frac{\frac{b}{b+c}}{\frac{b}{b+c} + \frac{c}{c+a}}(b+c) + \frac{\frac{c}{c+a}}{\frac{b}{b+c} + \frac{c}{c+a}}(c+a)\right)^{2/3}. \end{align} On the other hand, we have $$\Big(\frac{1+5a+5b}{5+a+b}\Big)^3 - (a+b)^2 = \frac{(a^2+2ab+b^2+18a+18b+1)(1-a-b)^3}{(5+a+b)^3} \ge 0$$ which results in $(a+b)^{2/3} \le \frac{1+5a+5b}{5+a+b}$.

Thus, it suffices to prove that $$\frac{a}{a+b}\frac{1+5a+5b}{5+a+b} + \Big(\frac{b}{b+c} + \frac{c}{c+a}\Big)\left(\frac{\frac{b}{b+c}}{\frac{b}{b+c} + \frac{c}{c+a}}(b+c) + \frac{\frac{c}{c+a}}{\frac{b}{b+c} + \frac{c}{c+a}}(c+a)\right)^{2/3} \le \frac{31}{27}.$$ It suffices to prove that $$\Big(\frac{31}{27} - \frac{a}{a+b}\frac{1+5a+5b}{5+a+b}\Big)^3\ge \Big(\frac{b}{b+c} + \frac{c}{c+a}\Big)^3\left(\frac{\frac{b}{b+c}}{\frac{b}{b+c} + \frac{c}{c+a}}(b+c) + \frac{\frac{c}{c+a}}{\frac{b}{b+c} + \frac{c}{c+a}}(c+a)\right)^2. $$ After homogenization, it suffices to prove that $$(a+b+c)^2\Big(\frac{31}{27} - \frac{a}{a+b}\frac{(a+b+c)+5a+5b}{5(a+b+c)+a+b}\Big)^3\ge \Big(\frac{b}{b+c} + \frac{c}{c+a}\Big)^3\left(\frac{\frac{b}{b+c}}{\frac{b}{b+c} + \frac{c}{c+a}}(b+c) + \frac{\frac{c}{c+a}}{\frac{b}{b+c} + \frac{c}{c+a}}(c+a)\right)^2.$$ If suffice to prove that $f(a,b,c) \ge 0$ for $a, b, c \ge 0; \ c = \min(a,b,c)$ where $f(a,b,c)$ is a polynomial (a long expression).

We apply the Buffalo Way. There are three possible cases:

1) If $c = 0$, we have $f(a,b, 0) = 216a(a+28b)(8a-19b)^2(a+b)^5 \ge 0$.

2) If $c > 0$ and $c \le a \le b$, let $a = c + s, \ b = c+s+t; \ s,t \ge 0$. $f(c+s, c+s+t, c)$ is a polynomial in $c, s, t$ with non-negative coefficients.

3) If $c>0$ and $c \le b\le a$, let $b = c+s, \ a = c+s + t; \ s,t \ge 0$. We have \begin{align} &f(c+s+t, c+s, c) = g(c,s,t) + 216(s+t)(29s+t)(11s-8t)^2(2s+t)^5\\ &\quad + 108(146777s^4+13368s^3t-97257s^2t^2+42286st^3+7200t^4)(2s+t)^4c \end{align} where $g(c,s,t)$ is a polynomial with non-negative coefficients. Note that $$146777s^4+13368s^3t-97257s^2t^2+42286st^3+7200t^4 \ge 2\sqrt{146777 \cdot 7200} s^2 t^2 + 2\sqrt{13368\cdot 42286}s^2t^2 - 97257s^2t^2 \ge 0.$$

The desired result follows. We are done.


Here is my personal take on the problem;

We can use the substitutions $b+c = 1-a$, $c+a = 1-b$, $c = 1-a-b$ to reduce the problem to the following inequality in arbitrary $a,b$;

$$\dfrac{a}{\sqrt[3]{a+b}} + \dfrac{b}{\sqrt[3]{1-a}} + \dfrac{1-a-b}{\sqrt[3]{1-b}} \leq \dfrac{31}{27}$$

Define $f(a,b) = \dfrac{a}{\sqrt[3]{a+b}} + \dfrac{b}{\sqrt[3]{1-a}} + \dfrac{1-a-b}{\sqrt[3]{1-b}}$. I suspect that using the first and second derivative tests to find local maxima-minima could solve the problem from here, as $\dfrac{\partial f}{\partial a}$ and $\dfrac{\partial f}{\partial b}$ are, while messy, not difficult to calculate.

In fact, this can be generalized quite a bit. This method can be generalized as follows;

Consider $\sum_{cyc} g(x_1,\dots,x_n)$ for some well-defined function $g$, where the cyclic behavior occurs over a set of variables $x_1,\dots,x_k$ for $k > n$ and we restrict these $x$ by stating that $\sum_{j=1}^k x_j = A$ for a fixed constant $A$. Then we can write $x_k = A - \sum_{j=1}^{k-1} x_j$ and use this as the basis for a substitution to create a function $f(x_1,\dots,x_{k-1}) = \sum_{cyc} g(x_1,\dots,x_n)$ with restrictions on the $x_j$ removed and using the substitution previously given for $x_k$. If $g$ is differentiable, then so will $f$ be, and so local extremes can be calculated. If $g$ is twice differentiable, then so is $f$ and we can use the second derivative test to test whether these values are true extrema or saddle points.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.